Step
*
1
2
2
2
of Lemma
mean-value-for-bounded-derivative
1. I : Interval
2. iproper(I)
3. f : I ⟶ℝ
4. f' : I ⟶ℝ
5. ∀x,y:{x:ℝ| x ∈ I} . ((x = y)
⇒ (f'[x] = f'[y]))
6. d(f[x])/dx = λx.f'[x] on I
7. c : ℝ
8. ∀x:{x:ℝ| x ∈ I} . (|f'[x]| ≤ c)
9. x : {x:ℝ| x ∈ I}
10. y : {x:ℝ| x ∈ I}
11. f'[x] continuous for x ∈ I
12. f[x] continuous for x ∈ I
13. e : {e:ℝ| r0 < e}
14. (x < y)
⇒ (|f[x] - f[y]| ≤ ((c * |x - y|) + e))
15. (y < x)
⇒ (|f[x] - f[y]| ≤ ((c * |x - y|) + e))
16. (|f[x] - f[y]| ≤ e) ∨ (r0 < |x - y|)
⊢ |f[x] - f[y]| ≤ ((c * |x - y|) + e)
BY
{ D -1 }
1
1. I : Interval
2. iproper(I)
3. f : I ⟶ℝ
4. f' : I ⟶ℝ
5. ∀x,y:{x:ℝ| x ∈ I} . ((x = y)
⇒ (f'[x] = f'[y]))
6. d(f[x])/dx = λx.f'[x] on I
7. c : ℝ
8. ∀x:{x:ℝ| x ∈ I} . (|f'[x]| ≤ c)
9. x : {x:ℝ| x ∈ I}
10. y : {x:ℝ| x ∈ I}
11. f'[x] continuous for x ∈ I
12. f[x] continuous for x ∈ I
13. e : {e:ℝ| r0 < e}
14. (x < y)
⇒ (|f[x] - f[y]| ≤ ((c * |x - y|) + e))
15. (y < x)
⇒ (|f[x] - f[y]| ≤ ((c * |x - y|) + e))
16. |f[x] - f[y]| ≤ e
⊢ |f[x] - f[y]| ≤ ((c * |x - y|) + e)
2
1. I : Interval
2. iproper(I)
3. f : I ⟶ℝ
4. f' : I ⟶ℝ
5. ∀x,y:{x:ℝ| x ∈ I} . ((x = y)
⇒ (f'[x] = f'[y]))
6. d(f[x])/dx = λx.f'[x] on I
7. c : ℝ
8. ∀x:{x:ℝ| x ∈ I} . (|f'[x]| ≤ c)
9. x : {x:ℝ| x ∈ I}
10. y : {x:ℝ| x ∈ I}
11. f'[x] continuous for x ∈ I
12. f[x] continuous for x ∈ I
13. e : {e:ℝ| r0 < e}
14. (x < y)
⇒ (|f[x] - f[y]| ≤ ((c * |x - y|) + e))
15. (y < x)
⇒ (|f[x] - f[y]| ≤ ((c * |x - y|) + e))
16. r0 < |x - y|
⊢ |f[x] - f[y]| ≤ ((c * |x - y|) + e)
Latex:
Latex:
1. I : Interval
2. iproper(I)
3. f : I {}\mrightarrow{}\mBbbR{}
4. f' : I {}\mrightarrow{}\mBbbR{}
5. \mforall{}x,y:\{x:\mBbbR{}| x \mmember{} I\} . ((x = y) {}\mRightarrow{} (f'[x] = f'[y]))
6. d(f[x])/dx = \mlambda{}x.f'[x] on I
7. c : \mBbbR{}
8. \mforall{}x:\{x:\mBbbR{}| x \mmember{} I\} . (|f'[x]| \mleq{} c)
9. x : \{x:\mBbbR{}| x \mmember{} I\}
10. y : \{x:\mBbbR{}| x \mmember{} I\}
11. f'[x] continuous for x \mmember{} I
12. f[x] continuous for x \mmember{} I
13. e : \{e:\mBbbR{}| r0 < e\}
14. (x < y) {}\mRightarrow{} (|f[x] - f[y]| \mleq{} ((c * |x - y|) + e))
15. (y < x) {}\mRightarrow{} (|f[x] - f[y]| \mleq{} ((c * |x - y|) + e))
16. (|f[x] - f[y]| \mleq{} e) \mvee{} (r0 < |x - y|)
\mvdash{} |f[x] - f[y]| \mleq{} ((c * |x - y|) + e)
By
Latex:
D -1
Home
Index